OpenGL iPhone games with Cocos2D - Moore, Todd (O'Reilly, 2010)
"Cocos2D is one of the best known and most utilized gaming libraries for the iPhone, iPad, and Mac. It is completely open source and free to use. If you are building a 2D iPhone game and need the power of OpenGL, then this is the library to learn. In this lesson, we will take the starting template provided by Cocos2D and create a game called Nuclear Fallout where you drive a tank to avoid lots of radioactive material falling from the sky. You will learn how to animate sprites, play sound effects and background music, create particle systems for cool explosion effects, and utilize touch and accelerometer controls. We'll also discuss how to optimize our game to increase frame rates."--Resource description page.